The Effect of Foot Massage on Decreasing Glucose Levels of Diabetes Types 2 Patients in Kalisidi Village - Eko Alwiyan; Siti Baitul Mukarromah (Universitas Negeri Semarang, 2022)
Research Approach Using Survey Methods with measurement techniques. The population of the study was 80 people, 31 men and 49 women. The sampling technique is purposive sampling. Data analysis used descriptive analysis techniques. The results of the study on the Body Mass Index (BMI) of the residents of Kalisidi Village in 2021 in the normal category of 45.71% (n=16), Pre-Obesity 42.85% (n=15), Obesity level I 11.42% (n=4). The results of the study showed that the blood sugar levels of the residents of Kalisidi Village were in the normal category 25.71% (n=9), pre-diabetes 17.14% (n=6) and the remaining 57.14% (n=20) in the diabetes category. Giving massage treatment and eating patterns showed a decrease in the average blood sugar level of men from 245.81 mg/dl to 204.45 mg/dl and the average blood sugar level of women from 222.45 mg/dl to 182.83 mg/dl. The conclusions of the study were the Body Mass Index (BMI) of the residents of Kalisidi Village in 2021 in the normal category of 45.71% (n=16), blood sugar levels in the normal category of 71.66% (n=43), and giving massage treatments and eating patterns showed results. a decrease in the average blood sugar level of men from 245.81 mg/dl to 204.45 mg/dl.